IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KEDISIPLINAN SISWA MELALUI KETELADANAN GURU - Muzammil, Muzammil; Bahrian, Bintang Indriyana (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2024)
This study discusses the implementation of the Kurikulum Merdeka (Freedom Curriculum) at Madrasah Aliyah Nahdlotul Ulama in enhancing student discipline through teacher role modeling. The Kurikulum Merdeka is designed to provide student-centered learning freedom, enabling students to develop competencies and character according to their needs. However, its implementation faces challenges with low student discipline.The results of this study indicate that the role of teachers as role models is crucial in shaping student discipline. Teachers' exemplary behavior helps students understand responsibility and make optimal use of learning freedom. A project-based learning approach and the integration of Islamic moral values are also key supporting factors in forming balanced student character. This study emphasizes the importance of a supportive school environment and teacher creativity to maximize the potential of the Kurikulum Merdeka